MINIMUM NORM FROM RECONSTRUCTED INPUT FOR NONMINIMUM-PHASE SYSTEM - (NIM : 20114010), SALMAN
Input reconstruction is used on a system if you want to determine the input if the output and its system are known. In the input reconstruction, the process is carried out by the inverse way, that is using the output system as input to the inverse model, assuming the transfer function is invertible. In the inverse process the reasearcher used Markov parameters to reconstruct the input. Many systems have not invertible transfer function, which is called nonminimum phase system. In this thesis, recontruction input will be done for nonminimum-phase system. Bounded input assumptions is needed to reconstruct the input using the extended and delayed system. In the process of input reconstruction with existed output, it is necessary to find an estimated system of is ^x to determine input estimation. The researcher used two methods to find ^x which are quadratic optimization method, and Generalized Inverse. Both methods the norm between the input estimation and actual input can be compared. The reasearcher also compared the output estimation with actual output. Generally, the result can be concluted that the process of input reconstructions using Generalized Inverse is better than using quadratic optimization method.